Numerical assessment of 3‐D macrodispersion in heterogeneous porous media. Issue 5 (22nd May 2013) - Beaudoin, A.; de, J.‐R.
Key Points Heterogeneity‐induced dispersion is much larger in 3D than in 2D Braiding of high‐velocity channels critically enhance transverse dispersion Longitudinal dispersion also comes from high correlations of the velocity field